HUBUNGAN KORDINASI MATA TANGAN DAN POWER OTOT LENGAN BAHU TERHADAP HASIL SERVIS ATAS SISWA YANG MENGIKUTI EKSTRAKURIKULER BOLA VOLI DI SMA NEGERI 1 RAMBAH HILIR - Sitepu, Ahmad Syukur; Zainur, Zainur; Sulastio, Agus (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract : The purpose of this research is to find out the hand eye coordination relationship and the shoulder arm muscle power to the ability overhand service of the students who join the extracurricular in SMA Negeri 1 rambah Hilir. The type of research in use is the type of correlation research, This research is a correlational research by comparing the measurements of two different variables in order to be able to determine the level of the relationship between these variables.The population in this research is 14 students who join volleyball Extracurrieler. The data retrieval technique in this research uses total sampling because it calculates a sample that is not too large, This test uses a correlation type, Then test the data using the normality test, Product Moments test, correlation, variable normality test X â‚ L â‚€ max (0.1379) < Ltable (0.227), Variable normality test X â‚‚ L â‚€ max (0.2148) < Ltable (0,227), And variable normality test Y L â‚€ max (0.1628) < Ltable (0.227). In other words the data is normal and research conclusions indicate where the relationship analysis result of correlation states there is a significant relationship together between the coordination of the hands eye and the muscle power of the arm and shoulders to the overhand service students who join the extracurricular in SMA 1 Rambah Hilir with r = (0,8869) > rtable = (0.553).Key Words : Hand eye , muscle Power arm and shoulder , overhand service, volleyball